2013
DOI: 10.1089/vbz.2012.1154
|View full text |Cite
|
Sign up to set email alerts
|

An Infant with Acute Brucellosis Presenting With Coombs-Positive Autoimmune Hemolytic Anemia: Is Breastfeeding Guilty for Transmission?

Abstract: Brucellosis is a zoonotic infectious disease that can be transmitted to humans through infected milk and dairy products. There are limited cases with Brucella infection acquired via breastfeeding in infants in the literature. Also, Coombs-positive autoimmune hemolytic anemia as a result of the disease is comparatively rare when considering the other frequent hematologic complications. We report a mother who acquired the infection as a result of consuming infected milk and dairy products after delivery and of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Human brucellosis has been associated with livestock contact, raw dairy food consumption and lack of access to health care (Bernard et al., ; Franco et al., ; Makita et al., ). There have also been instances of human‐to‐human transmission of brucellosis through breast milk of infected mothers to children (Palanduz et al., ; Apa et al., ) or through sexual intercourse (Kato et al., ). Human cases of brucellosis are tied to the disease in livestock, and reductions in brucellosis in livestock have resulted in reducing the number of human cases of the disease (Roth et al., ; Glynn and Lynn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Human brucellosis has been associated with livestock contact, raw dairy food consumption and lack of access to health care (Bernard et al., ; Franco et al., ; Makita et al., ). There have also been instances of human‐to‐human transmission of brucellosis through breast milk of infected mothers to children (Palanduz et al., ; Apa et al., ) or through sexual intercourse (Kato et al., ). Human cases of brucellosis are tied to the disease in livestock, and reductions in brucellosis in livestock have resulted in reducing the number of human cases of the disease (Roth et al., ; Glynn and Lynn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among reported forms of transmission we found breastfeeding and more exotic forms, such as bone marrow transplantation and aerosolization of the involved bacterium . In this review, 61% of patients were infants, reported as HHT by vertical transmission or during breastfeeding . Of the 47 patients, the transplacental route ranked as the most common form of HHT (with 11 total patients).…”
Section: Discussionmentioning
confidence: 87%
“…Breast milk is a potential source of infection, though it is frequently overlooked. [5] Clinical manifestations of childhood brucellosis are varied and range from minimal symptoms to extreme morbidity and occasional fatality. [6] Also, its clinical features are protean and simulate those of other febrile illnesses.…”
Section: Discussionmentioning
confidence: 99%